TOTAL QUALITY MANAGEMENT PADA BALAI LATIHAN PENDIDIKAN TEKNIK GMIM KAATEN TOMOHON DI KOTA TOMOHON - Korompis Meggi Leddy Meylan; Celcius ., Talumingan; Leonardus R. Rengkung (AGRI-SOSIOEKONOMI, 2017)
The aim of this research is to know the application of Total Quality Management at Technical Training Center (BLPT) GMIM KAATEN TOMOHON. The study was conducted from February to April 2017. The data used in this study are primarily qualitative data relating to the measurement of Total Quality Mananagement, consists of Customer Focus data, Obsession with quality, Long-term commitment, Team Work, Education and training. Data collection uses a list of questions to be asked directly to the management and employees and Consumers. The results of the study and discussion on the application of Total Quality Management to the customers and to the leadership and employees of BLPT GMIM Kaaten Tomohon indicate that included in the highly satisfied category are Obsessions on Quality, Long Term Commitment, Teamwork, and for Education and Training. While the included in the category of satisfaction is Focus on Customers.